The essential role of CCT2 in the regulation of aggrephagy - Luo, Jie; Feng, Ze-Sen; Tang, Ji-Xin (Frontiers in Aging Neuroscience, 2024)
Protein aggregation, a defining characteristic of numerous human diseases, poses a significant challenge to cellular health. Autophagy, an essential cellular recycling process, specifically targets and degrades these harmful protein aggregates through a specialized mechanism known as aggrephagy. However, the precise mechanisms underlying the exquisite selectivity of aggrephagy in identifying and eliminating only aggregated proteins while sparing healthy cellular components have remained enigmatic. Here, in this mini review, we highlights the essential role of CCT2, a subunit of the chaperonin TRiC complex, in regulating aggrephagy. CCT2, traditionally viewed as a molecular chaperone, has emerged as a novel autophagy receptor that specifically targets solid protein aggregates for degradation. This ubiquitination-independent mode of recognition by CCT2 expands our understanding of protein degradation pathways. The functional switch of CCT2 from a chaperone to an autophagy receptor underscores its dynamic nature and ability to adapt to cellular stress. The selectivity of CCT2-mediated aggrephagy for solid aggregates has implications for neurodegenerative diseases. Further research is warranted to explore the therapeutic potential of enhancing CCT2-mediated aggrephagy in such diseases.